The Future of Financial Auditing: An Innovative Approach with Autonomous Systems and Blockchain - REHNEMA, RADİN (International Journal of Business Management and Entrepreneurship, 2025)
The rapid digitization of global finance has fundamentally altered the landscape of financial auditing. Emerging technologies—particularly autonomous systems and blockchain—are reshaping the way audits are planned, executed, and evaluated. This study investigates how the integration of artificial intelligence, robotic process automation (RPA), and distributed ledger technologies (DLT) can lead to a more transparent, efficient, and secure auditing ecosystem. Through an extensive literature review and analysis of current audit frameworks, this research outlines the potential of autonomous audit agents to perform real-time data analytics, anomaly detection, and continuous monitoring without human intervention. Additionally, the immutable and decentralized nature of blockchain is explored as a foundational infrastructure for audit trails, smart contracts, and trustworthy financial disclosures. The methodology employed is qualitative and exploratory in nature, drawing from recent case studies, scholarly articles, and international accounting standards (e.g., IFRS 9, IFRS 15). Findings suggest that while these technologies significantly enhance audit efficiency and fraud detection capabilities, challenges such as regulatory gaps, ethical concerns, and technical scalability remain. The discussion highlights the shifting role of auditors—from compliance enforcers to strategic interpreters of intelligent systems—and underscores the need for new governance models, cross-disciplinary education, and standardized digital audit protocols. Ultimately, this paper offers forward-looking recommendations to policymakers, auditors, and educators for adapting to the evolving audit landscape. By embracing innovation responsibly, the audit profession can strengthen public trust, improve accountability, and maintain relevance in the digital financial era.